PERAN KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL DALAM MENINGKATKAN KINERJA WIRAUSAHA - Ariyanti, Yulekhah (Laporan Penelitian dan Pengabdian Masyarakat, 2024)
ABSTRACT Improved performance of the entrepreneur need to do to optimize their work, where the performance is determined by the ability to manage intellectual property in controlling emotions in interaction with others and the level of spiritual intelligence. This study aimed to analyze the influence of Intellectual Intelligence, Spiritual Intelligence and Emotional Intelligence in Improving entrepreneur Performance at Central Java. Researchers deploy the questionnaire by 90 exemplar according to population size. Of the 90 exemplar questionnaires distributed, 75 of them returned from 75 questionnaires returned only 71 were complete and worth analyzing. Regression Analysis with SPSS 17.0 for windows used to test the significance of the effect of independent variables on the dependent variable and test the research model. The results showed that the Intellectual Intelligence significant positive effect on entrepreneur performance with regression coefficients for 0,315 and 0,001 significance